Implications of sand mining on the environment and livelihoods in Brong Ahafo Region - Baba, Salifu (2017)
A thesis submitted to the Department of Geography and Rural Development, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Philosophy in Geography and Rural Development,